TYPES OF SEMANTIC RELATIONS BETWEEN PHRASES - Shakhlo Akmal kyzy Asadova (Bright Mind Publishing, 2025)
It is known that each discipline that studies language has its own connection with it. This connection is determined by what aspect of language a particular social science studies. Language is a set of units prepared in advance for all members of a given society and serving to express a common and obligatory thought for all and for other purposes, as well as the laws of unification of these units. This interpretation of language proves that it is a psychophysical phenomenon that embodies such qualities as community, essence, possibility, and reason. Language manifests these properties in specific forms – in the form of specific phenomena and events. These include phrasemes and semantic relations between phrasemes. After all, language and each concept associated with it have their own unique nuances.
Keywords: Language, speech, community, particularity, phrase, expression, interphrase relations.